12 Improving teamwork in a paediatric clinical emergency team. (22nd November 2019) - Hunt, Paul; Skellett, Sophie
Abstract : Team working errors are known to contribute to poor outcome from cardiac arrest. Common errors: miscommunication, staff not attending, equipment problems and skills and knowledge gaps. 1 2 Subjective and objective feedback from CET events at our institution echoed many similar issues. Interventions and method: Routine twice daily CET huddles: red badges with team roles allocated, roles of each member outlined on back of badge, introductions with discussion of skills. Team leader role renamed 'team co–ordinator' (emphasising co–ordinating role to encourage team members to contribute). Team member allocated to manage situational awareness and evaluate quality CPR Regular CET simulation (SIM) practice. Feedback of issues prior to changes included: delay at start of emergency events when no–one was sure who was on the team or of skills of each team member; reluctance team members to act or speak up unless invited by team leader; lack environmental management – noise, equipment; lack of quality CPR monitoring. 6 months after implementation members of the CET were surveyed to get their views. Outcomes from events were monitored. Results: 6 months following implementation all patients with cardiac arrest achieved ROSC (small numbers but an encouraging start). Survey: 90% felt team cohesion improved 80–90% CET team members believed team behaviour better co–ordinated > 55% felt more confident at an event 70% felt communication among team members had improved 80% felt CET SIMs were beneficial 55% valued change Team Leader to team co–ordinator 45% believed better adherence to new interventions was needed to improve further Conclusion: Novel interventions to improve team working during clinical emergency events have seen improvements in team confidence and performance; with time we may see further objective evidence of improvement in clinical outcomes. Reference: Ornato JP, et al. Impact of Resuscitation System Errors on survival from In-hospital cardiac arrest. Resusciatation 2011 September;83(1):63-9.